Immunoglobulin A proteases in gram-negative bacteria isolated from human urinary tract infections. - Milazzo, F H (1984)
Several strains of gram-negative bacteria (seven genera, eight species) isolated from patients with urinary tract infections were found to hydrolyze myeloma immunoglobulin A (IgA) protein. Human IgG and IgM and colostrum IgA were not degraded by these organisms. Examination of cleavage digests showed two fragments of different electrophoretic mobilities, with antigenic reactivity and sodium dodecyl sulfate polyacrylamide gel electrophoresis profiles consistent with their identification as Fc and Fab components. The immunoelectrophoresis patterns of cleavage digests suggested that the proteases responsible for this hydrolysis may be dissimilar in the specificity of their IgA cleavage sites.